MICROBIOLOGICAL ANALYSIS OF PATHOGENS IN PATIENTS WITH SKIN CANCER - Khodirov Otabek Abdullaxayevich; Rakhimova Zulhumor Muhammadjon kizi (Web of Journals Publishing, 2025)
In this study, microbiological investigations were conducted on 10 patients diagnosed with skin cancer. The obtained data indicate that microorganisms play a significant role in oncological processes of the skin. As a result, the presence of Staphylococcus aureus, Propionibacterium acnes, and Human Papillomavirus (HPV) infections was detected in tumor lesions.
Keywords: Skin cancer, biopsy, HPV, Staphylococcus aureus, bacterial infection, inflammation, pathogen, bacteria, virus, fungus.